EPID-15. GUIDELINES FOR THE OPTIMAL USE OF SOCIAL MEDIA FOR NEURO-ONCOLOGISTS. (11th November 2019) - Hamidi, Nima; Mansouri, Alireza
Abstract: BACKGROUND: Approximately 80, 000 new Americans are diagnosed with a brain tumor annually. Social media (SM) has emerged as a powerful tool for patient empowerment. Its effective utilization by healthcare professionals is vital for better connection to patients and dissemination of evidence-based information. OBJECTIVES: To develop guidelines for optimal utilization of SM by neuro-oncologists, through a review of user engagement with content posted on SM relating to brain tumors. METHODS: Facebook (FB) and Twitter (TW) were searched using the term Brain Tumor . Page/account information such as user type, media (image/video) utilization in posts, and audience size (likes / followers) were recorded. Average activity and account annual growth (AAG) were calculated. Top qualitative themes were assigned. Correlations were assessed with Pearson's test. RESULTS: FB was predominantly used by organizations (64% of accounts) and provided a larger audience (67 pages, 581 likes) than TW (25 accounts, 67, 295 followers), which had similar proportion of personal (44%) and organizational accounts (52%). Charity & Fundraising (67%) was the top FB theme. Education & Research (72%) was the top TW theme. In FB, the page's annual growth (PAG) was not related to rate of monthly posting or the length of activity on FB, but presence on other concurrent platforms (Rho: 0.59) was influential for PAG and audience size (p < 0.05). In TW, quantity of monthly tweets (Rho: 0.66) and media utilization (Rho: 0.78) significantly correlated with audience size and AAG (p-values < 0.05). CONCLUSION: A multi-platform SM presence and use of relatable images/videos have a strong impact on both FB and TW engagement. FB is a stronger platform for organizations valuable for charity and fundraising. Multi-platform presence is more important than frequent posts on FB. TW is equally used by organizations and individuals, serving as an excellent medium for dissemination of research and educational material.